Danielle Walker's healthy in a hurry : real life, real food, real fast - Walker, Danielle (Chef); Pick, Aubrie (Ten Speed Press, 2022)
"These recipes and techniques will change the way you think about healthy food. It truly can be prepared without a lot of stress and everything is so tasty that you'll want to serve these dishes to your family or whole community-whether they eat a standard diet or one that's gluten-free, dairy-free, or otherwise allergy-free!"--